Stable Control Strategy for Planar Multi-link Underactuated Mechanical System with Non-zero Initial Velocity - HUANG Zixin; HOU Mengyu; QIN Xiangyu; WANG Lejun (Journal of Harbin University of Science and Technology)
Aiming at the stability control problem of planar multi-link underactuated manipulator system with non-zero initial velocity of last passive joint, a stable control strategy based on model reduction and open-loop iterative control is presented. According to the structural characteristic of this planar multi-link underactuated system, the original system model is reduced to a planar virtual two-link underactuated system by using the method of model reduction. Considering the existence of the nilpotent approximation characteristic of the reduced system, the open iterative controllers are designed to drive this planar virtual two-link underactuated system to its target states. At the same time, the end joint of planar multi-link underactuated manipulator also reaches its target position. Finally, the planar multi-link underactuated manipulator system with different structural parameters is selected for simulation experiments. The experimental results verify the effectiveness of the proposed control method.